Study of perinatal outcome of labour complicated with meconium stained liquor - Patil, Asmita N.; Inamdar, Misbah M.; Senapati, Jaynarayan B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Meconium stained amniotic fluid occurs in 9 to 20% of deliveries. It has long been implicated as a factor influencing foetal wellbeing during the intrapartum and postpartum period. Many authors have suggested that the type and the time of passage of meconium are most significant factors affecting foetal outcome. This study was carried out to find out the effect of meconium stained liquor during labour and its perinatal outcome. Methods: This prospective cross sectional and comparative study was carried out in a tertiary care hospital over a period of 1 year. The study group comprised of 118 women having MSAF during labour and the comparative group of 118 women with clear amniotic fluid which were randomly selected. The demographic data, obstetrical history, intrapartum findings and Apgar score were documented on predesigned proforma. Data collected was analysed using student t-test, chi square test, Z test for comparison of proportions and coefficient of variation for comparison of consistency of distributions. Results: Out of 1192 cases studied 118 cases showed presence of meconium stained liquor (9.89%). Caesarean section was performed in 41.52% cases with meconium stained liquor versus 31.35% in clear liquor group. Apgar score at 1 minute was significantly lower in meconium stained liquor (p<0.01). In meconium stained liquor group 42.37% foetuses had normal, 36.44% had suspicious and 21.18% had abnormal heart rate patterns respectively. There was no significant difference in the number of cases requiring NICU admission in meconium stained liquor (14.4%) and clear liquor groups (9.3%) (Z=1.214, P>0.05). Conclusions: Meconium staining is a commonly observed phenomenon. labour complicated with thick meconium stained liquor should ideally be categorised in to high risk obstetrics and managed in tertiary care with consultant obstetrician, consultant neonatologist and NICU in order to improve the perinatal outcome.